Rapid Discovery of a Photocatalyst for Air Purification by High‐Throughput Screening. Issue 9 (24th July 2014) - Sun, Song; Zhang, Fan; Qi, Zeming; Ding, Jianjun; Bao, Jun; Gao, Chen
Abstract Despite several decades of intensive studies, only a few commercial photocatalysts have been discovered by means of the conventional one‐at‐a‐time synthesis and characterization. Herein, a high‐throughput screening of photocatalysts for air purification using an infrared microscope, equipped with a set of homemade in situ gas reaction cells and a gas dosing system, is described. 1.0 % La3+/0.4 % Nd3+‐TiO2 was rapidly selected as an active photocatalyst for toluene degradation with a mineralization rate of 93.4 % at a humidity level of 70 % in 2 h. The excellent agreement between our combinatorial results and those of the bulk samples confirms the reliability of the developed rapid screening method. In addition, the investigation of the effects of pretreatment with NH3 and H2S on the photocatalytic activity also offers some information about the surface modification for air purification.